2001
DOI: 10.1109/42.952730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of center-line extraction algorithms in quantitative coronary angiography

Abstract: Objective testing of centerline extraction accuracy in quantitative coronary angiography (QCA) algorithms is a very difficult task. Standard tools for this task are not yet available. We present a simulation tool that generates synthetic angiographic images of a single coronary artery with predetermined centerline and diameter function. This simulation tool was used creating a library of images for the objective comparison and evaluation of QCA algorithms. This technique also provides the means for understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Analysis on the vessel level includes tasks such as segmentation of blood vessel regions [1], [2], [3] and vessel center extraction [4], [5]. Analysis and tracking of circulating cells/particles includes the detection and/or tracking of leukocytes (white cells) [6], [7], [8], [9], [1], [10] and erythrocytes (red blood cells) [11].…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis on the vessel level includes tasks such as segmentation of blood vessel regions [1], [2], [3] and vessel center extraction [4], [5]. Analysis and tracking of circulating cells/particles includes the detection and/or tracking of leukocytes (white cells) [6], [7], [8], [9], [1], [10] and erythrocytes (red blood cells) [11].…”
Section: A Backgroundmentioning
confidence: 99%
“…As a pre-processing step the vessel center-line is extracted. A good review on vessel center-line extraction is given in [4]. After testing several approaches we found that the skeleton algorithms proposed in [5], [30] are simple for implementation and yield robust and accurate results (see Fig.…”
Section: 'Virtual Flow' Computationmentioning
confidence: 99%
“…Traditionally, digital subtraction angiography (DSA) projection images have been the gold standard for stenosis grading. The shortcomings of visual assessment of these types of images have motivated the development of automated techniques to support vessel analysis [1,2], which has resulted in programs such as quantitative coronary angiography (QCA) [3]. Nowadays, the required image data for diagnostic purposes regarding vessels is increasingly acquired using techniques such as magnetic resonance angiography (MRA) and computed tomography angiography (CTA) [4,5], which are minimally invasive and yield three-dimensional (3D) image data.…”
Section: Introductionmentioning
confidence: 99%
“…However, 3D central lines on surfaces in paleontological context, especially for fossil oysters using photogrammetric technology, are not yet reported in the literature. Our algorithm is similar to the algorithms that use Delaunay (1934) triangulation andVoronoi (1908) The terms central line, skeleton and medial axis are used often in literature to describe related things (Greenspan et al, 2001;Palagyi et al, 2001). The terms central line and medial axis appear most often concerning thinning of the object on the surface such as road (Doucette et al, 2004).…”
Section: Related Workmentioning
confidence: 99%